THE INFLUENCE OF SERVICES, FACILITIES AND LOCATIONS TO PURCHASING DECISIONS AND CUSTOMER SATISFACTION ON WARKOP DEWA SIDOARJO - Dewi Setyoningrat; I Gede Arimbawa; Elok Damayanti (Journal of World Conference (JWC), 2019)
The purpose of this study was to analyze the influence of service, facilities, and location on purchasing decisions and customer satisfaction. Type of research is quantitive. The population of this study was 100 respondents who visited warkop Dewa Sidoarjo . The analysis technique used Partial Least Square (PLS). Data obtained from questionnaires and tested with SmartPLS 3.0 application. The results of this study indicate that services, facilities and locations have a positive and significant influence on purchasing decisions and customer satisfaction. Purchasing decisions have a positive and significant influence on customer satisfaction.